Farnesylated nuclear proteins Kugelkern and Lamin Dm0 affect nuclear morphology by directly interacting with the nuclear membrane - Polychronidou, Maria; Hellwig, Andrea; Grosshans, Jörg (Molecular biology of the cell, 2010)
Nuclear shape changes are observed during a variety of developmental processes, pathological conditions, and ageing. The mechanisms underlying nuclear shape changes in the above-mentioned situations have mostly remained unclear. To address the molecular mechanism behind nuclear shape changes, we analyzed how the farnesylated nuclear envelope proteins Kugelkern and lamin Dm0 affect the structure of the nuclear membrane. We found that Kugelkern and lamin Dm0 affect nuclear shape without requiring filament formation or the presence of a classical nuclear lamina. We also could show that the two proteins do not depend on a group of selected inner nuclear membrane proteins for their localization to the nuclear envelope. Surprisingly, we found that farnesylated Kugelkern and lamin Dm0 protein constructs change the morphology of protein-free liposomes. Based on these findings, we propose that farnesylated proteins of the nuclear membrane induce nuclear shape changes by being asymmetrically inserted into the phospholipid bilayer via their farnesylated C-terminal part.
Gesehen am 04.05.2023